Bantuan Kemanusian Korban Bencana Banjir di Kota Parepare - Andi Indah Anggerwati; Siti Diva Syarifah Lukman (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Community Service Activities (PKM) carried out by the Andi Sapada Institute of Social and Business PKM team in the form of providing humanitarian assistance to flood victims in Pare-Pare City. The flooded villages are in the Kelurahan Lompoe, Watang Bacukiki Sub-District, Lapadde Sub-District, Bumi Harapan Sub-District, Lumpue Sub-District, Galung Maloang Sub-District, Kampung Baru Sub-District, Tiro Sompe Sub-District, and Ujung Baru Sub-District.Fundraising for residents affected by the flood disaster in Pare-Pare City is one of the social activities carried out by the Andi Sapada Institute of Social Sciences and Business Student Executive Body in collaboration with the Provincial Government of Central Sulawesi. Providing assistance is carried out in flood-prone areas by taking four location points. This location was chosen based on the conditions and characteristics of flood-prone areas, which are characterized by differences in flood intensity, number and population density, and reliability. Considering the impact caused by the natural disaster was severe enough to take lives, the academic community had the initiative to raise donations in the form of groceries, clothing, and money. The donors came from the academic community of the Andi Sapada Institute of Social Sciences and Business, especially within all Faculties on Campus. With this activity, it is hoped that the assistance provided can meet the needs and ease the burden on the affected community, especially in the midst of current conditions.